OVERVIEW OF PEDIATRIC NURSING: PARENTAL ATTITUDES AND PEER RELATIONS IN EARLY CHILDHOOD - ERDOGDU, Ozge; CETINKAYA, Senay (Socrates Journal of Interdisciplinary Social Studies, 2022)
Early childhood is called as preschool period. What they experience during this period can change the development of the children and the quality of their life; these experiences may leave lasting traces in children’s life. The early years of childhood are important for personality development and each developmental period has difficulties to overcome. It is essential to support the social development of the child in the first and early childhood periods and it is necessary to raise self-confident individuals who are successful in communicating with their environment when the foundations of personality development are laid. In this period, parental attitudes, peer relationships, effective behavior in peer relationships are important in the development of the child. Parents need to know the basic needs of children and distinguish the differences in the child’s development period, providing the environment where the child will feel safe by meeting their socio-emotional, mental and physical needs. Raising awareness, training and counseling are among the roles of Pediatric Nurses. Mother and father are role models for their children. Parents’ attitudes and behaviors have been the subject of studies in order to analyze the relationship of parents with the psychosocial adjustment of the child correctly. Parental attitudes are “Democratic”, “Authoritarian”, “Overprotective” and “Permissive”. In early childhood, peers come after the family for the child. Effective forms of behavior in peer relationships are social timidity, social acceptance, problem solving, social behavior and aggression. The interaction between peer groups plays an important role in the child’s healthy personality development and socialization process. In this review, parental attitudes in early childhood, the importance of peer relationships for child development, effective forms of behavior in peer relationships, and the role of pediatric nurse are discussed in the light of the literature.